2011
DOI: 10.1111/j.1365-2052.2011.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of 260 microsatellite loci in the domestic goat, Capra hircus

Abstract: OR. Five markers were significant (P < 0.05) for WEI; only one THRSP SNP remained significant following Bonferroni correction (Table 1).Comments: The current study emphasized genes with lipogenic activity and their relationship to reproductive events. Weaning-to-oestrus interval was associated with five SNPs. A single THRSP SNP maintained an association with WEI after correction testing. THRSP has been identified as a murine candidate gene within overlapping QTL for the effects of lifetime fertility and dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A large number of these hypervariable markers is available in goat (Seki et al, 2012), however, their genotyping and scoring are labour intensive, and allele size calling is difficult to be calibrated across apparata and laboratories, in the absence of a substantial number of shared samples.…”
Section: Development Of High-throughput Snp Assays For the Analysis Omentioning
confidence: 99%
“…A large number of these hypervariable markers is available in goat (Seki et al, 2012), however, their genotyping and scoring are labour intensive, and allele size calling is difficult to be calibrated across apparata and laboratories, in the absence of a substantial number of shared samples.…”
Section: Development Of High-throughput Snp Assays For the Analysis Omentioning
confidence: 99%
“…We extracted DNA from 214 fecal samples, and confirmed the PCR amplification of the Cytb gene in 192 feces-derived DNA samples. Microsatellite regions were isolated using a standard procedure (Glenn and Schable, 2005;Seki et al, 2012). Approximately 5 µg genomic DNA was digested with XmnI and RsaI restriction enzymes (New England Biolabs Japan Inc., Sumida-ku, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The purified PCR-products were ligated to the pT7Blue T-vector (Novagen, Madison, WI, USA), and transformed into ECOS-competent Escherichia coli JM109 (Nippon Gene, Chiyoda-ku, Tokyo, Japan). The cloned inserts were amplified and sequenced using the universal M13 primers, P7 and P8 (Seki et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The amplification of DNA using the SuperSNX linker primer is biased against producing small PCR products, and PCR products obtained after enrichment can be cloned directly without contaminating a large proportion of the small DNA fragments [19]. We succeeded in developing 260 novel microsatellite loci using hybridization with biotinylated microsatellite oligonucleotide (TG) 12 or (AG) 12 probes [11]. These developed markers were composed of two types of repeat motifs containing interrupted DNA sequences: 15 markers contained compound repeats such as (CA) n and (AT) n , and 243 were composed of simple repeats such as dinucleotide motifs (239 markers), trinucleotide motifs (two markers), tetranucleotide motifs (one marker), and heptanucleotide motifs (one marker).…”
Section: Development Of Microsatellite Markers In Goatsmentioning
confidence: 99%
“…In particular, information regarding the number and chromosomal location of goat genetic markers is limited. Although in a previous study we developed a large number of new microsatellite markers [11], these were insufficient for linkage analyses of phenotypic traits. Recently published studies have reported on whole-genome mapping technologies [12] and on the sequencing data of the goat genome obtained by integrating next-generation sequencing [10].…”
Section: Introductionmentioning
confidence: 99%